Burnout and Maladjustment Among Employed Students - Drăghici, Gabriela-Lăcrămioara; Cazan, Ana-Maria (Frontiers in Psychology, 2022)
Stress and burnout are present in every aspect of an individual’s life, and the growing number of employed students raises certain concerns about their engagement in academic tasks and finishing their studies. Our study aims to analyze the differences between student burnout in different contexts, work- and academic-related burnout, and examine the predictive role of burnout in academic maladjustment, including test anxiety as a mediator and occupational status as a moderator. The sample consisted of 151 students from different universities in Romania. Consistent with previous studies, the results showed that academic burnout is higher than work-related burnout. High levels of test anxiety explain high levels of academic burnout, which in turn explains low levels of academic adjustment. The results highlight the mediating role of anxiety in the relationship between academic burnout and academic maladjustment with occupational status as a moderator. Future research should focus on the type of students’ job, the mediating relationship between self-efficacy and academic burnout, and the relationship between burnout and personality traits.